A Kraljic and competitive rivalry perspective on hospital procurement during a pandemic (COVID-19): a Dutch case study. Issue 1 (23rd August 2021) - Tip, Barbara; Vos, Frederik Guido Sebastiaan; Peters, Esmee; Delke, Vincent
Abstract : Purpose: Procurement professionals widely use purchasing portfolio models to tailor purchasing strategies to different product groups' needs. However, the application of these approaches in hospitals and the impact of a pandemic shock remain largely unknown. This paper aims to assess hospital purchasers' procurement strategies during the COVID-19 pandemic, the effects of factor-market rivalry (FMR) on strategies and the effectiveness of purchasing portfolio categorizations in this situation. Design/methodology/approach: This qualitative study of hospital purchasing in the Netherlands is supported by secondary data from official government publications. Semi-structured interviews were conducted with 13 hospital purchasers at large hospitals. An interpretative approach is used to analyze the interviews and present the results. Findings: The findings reveal that product scarcity forces purchasers to treat them as (temporary) bottleneck items at the hospital level. The strategies adopted largely aligned with expected behavior based on Kraljic's commodity management model. Adding the FMR perspective to the model helped to further cluster crisis strategies into meaningful categories. Besides inventory management, increasing supply, reducing demand and increasing resource coordination were the other common strategies. An important finding is that purchasers and governments serve as gatekeepers in channeling FMR, thereby reducing potential harmful competition between and within hospitals. Social implications: The devastating experience of the COVID-19 pandemic is unveiling critical weaknesses of public health-care provision in times of crisis. This study assesses the strategies hospital purchasers apply to counteract shortages in the supply chain. The findings of this study emphasize the importance of gatekeepers in times of crisis and present strategies purchasers can take to assure the supply of resources. Originality/value: No research has been conducted on purchasing portfolio models and FMR implications for hospitals during pandemics. Therefore, the authors offer several insights: increasing the supply risk creates temporary bottleneck strategies, letting purchasers adopt a short-term perspective and emphasizing the high mobility of commodities in the Kraljic commodity matrix. Additionally, despite more collaboration uncovered in other studies regarding COVID-19, strong rivalry arose at the beginning of the pandemic, leading to increased competition and less collaboration. Given such increased FMR, procurement managers and governments become important gatekeepers to balance resource allocation during pandemics both within and between hospitals.